SIGHTSEEING PLANNING SUPPORT SYSTEM ADOPTING GAMIFICATION (Proceedings of the International Conference on Hospitality and Tourism Management, 2022)
In recent years, it has been easier to obtain various information on the Internet, and people have to select appropriate information from among the large amount of information available. This can also be said about sightseeing information. As it is difficult for tourists to find the information that suits their purposes by themselves, a system that effectively provides the appropriate information to them is necessary. On the other hand, in order to provide users with real-time information, it is necessary to urge them to continue using the system, and it is effective to adopt gamification to increase users’ motivation to continuously utilize the system. Against the above backdrop, in order to support users’ enjoyment in creating efficient and pleasant sightseeing plans, this study aims to develop a sightseeing planning support system that incorporates gamification to increase motivation and combines with web-geographic in-formation systems (Web-GIS) and sightseeing planning and sharing system. The system was operated over a period of seven weeks in Chofu City, in Tokyo Metropolis, Japan. Based on the results of a questionnaire survey for 51 users, though the operability of the 3 main functions incorporated with motivation by gamification was rated lower than those of the 2 basic functions, their use-fulness was highly rated. Based on the results of the access log analysis, it was effective to design the system so that the same functions can be used regardless of the type of information terminal. Additionally, it was evident that the continuous utilization of the system could increase the number of sightseeing plans made by the users.
Keywords: sightseeing planning support system; gamification; sightseeing plan making and sharing system; web geographic information systems(Web-GISs)